Innovación, Organización y Marketing (2013)
Leonard Di Vici, in 1490, put into plans an idea that for the time was absurd and unviable, which consisted in imagining human beings taking flight in mechanical devices, many of the critics of that time judged him for wanting to go against of the designs of God "If God had wanted us to fly we were blessed with wings like birds", it took more than four centuries for that idea to evolve and thanks to the changes suffered by the cultural and technological paradigms over the years , the opportunity was generated that allowed Paul Cornu in 1907 to exhibit a prototype helicopter that only rose to the height of the forehead of an adult human being. The criticism was immediate and many considered a waste of time and resources this idea, it was more an expensive toy than something whose utility could be considered in the market. However, the evolution, what we know as the helicopter today, did not have to take as long as from the idea that Di Vinci illustrated and in 1939 Igor Sikorsky stabilized the artifact and could get it to stay in the air thanks to a second engine that strategically located began a revolutionary product, whose application began to be used in the war.